A Study on Performance of Financial Institutions in Ghana - Irbad, Husein Mohamed (Archives of Business Research, 2023)
The aim of this study is to investigate the performance of Ghanaian financial institutions. This study has used four proxies intended to measure the performance of financial institutions namely: financial access, financial depth, financial efficiency and financial stability. The overall proxies are consisted of thirty variables. In the study, there are four objectives: measuring service of financial access in Ghanaian financial institutions is the first one. The second objective is to examine the size of Ghanaian financial institutions. The third and fourth objectives are to measure the efficiency and stability of Ghanaian financial sector. We created a development of financial performance model describing the variables in this study. The main analysis of the study is Mean calculation and Weighted Least Squares Multiple Regression Analysis (WLS.) This study investigated secondary data. The data was analyzed by using Statistical Package for Social Sciences (SPSS) in descriptive statistics and Excel Software. The result showed significance in financial access (F= 43.352 P= .000) with r-value (r= 949**) and financial depth (F= 42.973 P= .000) with r-value (r= 925**) while financial efficiency and stability showed insignificance. This holistic study that combined access, depth, efficiency and stability proved that Ghanaian financial institutions are inefficient and there is instability as well.